Quranic Messages on Environmental Sustainability: an Expository Study of Its Relevance - Muhamad, Asmawati; Syihab, Abdul Halim; Achour, Meguellati (Brill Academic Publishers, 2019)
The contemporary discourse of environmental sustainability has many values embedded in the teachings of the Quran and Sunna. The general outlook of the Quranic paradigm on utilizing the natural environment is based on the prohibition of aggression and misuse, as well as being founded on ideas of construction and sustainability. Unfortunately, in the contemporary world the Muslim community fails to pay sufficient attention to the relevant instructions in the Quran and Sunna. Thus, this article attempts to expand on key concepts within the Quran and Sunna which reveal the most important values for environmental sustainability. The research methodology employed in this paper is an analytical study of a number of Quranic verses with a particular focus on tafsir bi al-ma t-ur (explanation based on hadith), tafsir bi al-ra yi (explanation based on reason), and historical narrative. In short, this paper brings to light the importance of relevant classical and contemporary Quran and Sunna studies for improving human-nature relations and coexistence. © koninklijke brill nv, leiden, 2019.